2015
DOI: 10.14798/73.2.804
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT DOSES OF SYNTHETIC HORMONE LHRH-A2 ON SERUM SEX HORMONES, OVULATION PERCENT AND EGG HATCHING RATES OF PERSIAN STURGEON Acipenser persicus

Abstract: Acipenser persicus is one of the economically valuable fishes in the Caspian Sea. Due to the economical and cultural importance of sturgeons in the world, understanding of sturgeon reproduction is necessary for successful management of their populations in aquaculture and nature. To improve the culture methods and to facilitate captive breeding programs to support restocking, it is necessary to understand the changes in steroid hormones during artificial reproduction. The administration of sturgeon luteinizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In the current study, a positive effect of rGnRH treatment was displayed on the number of eggs per gram. It was consistent to previous research on Persian sturgeon, showing that increasing the LHRH-A2 levels from 4 to 6 µg kg -1 BW also increased the number of eggs per gram (Mohammadi et al, 2015). The egg quality and quantity from induced spawning appear to be partially related to the interaction between the stage of maturity or oocyte diameter and GnRHa dose (Ibarra and Duncan, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, a positive effect of rGnRH treatment was displayed on the number of eggs per gram. It was consistent to previous research on Persian sturgeon, showing that increasing the LHRH-A2 levels from 4 to 6 µg kg -1 BW also increased the number of eggs per gram (Mohammadi et al, 2015). The egg quality and quantity from induced spawning appear to be partially related to the interaction between the stage of maturity or oocyte diameter and GnRHa dose (Ibarra and Duncan, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, the methods of hypophysial and hormonal injections are widely used in fish-breeding for stimulation of oocytes maturing and ovulation process [63][64][65][66][67][68][69]. It is shown that the result depends on conditions of incubation and application of hormonal preparations [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was first developed in Japan in the 1950s for reversing the sex of aquarium fish and carp species and commercialized in the 1970s (Baroiller and D'Cotta, 2000). In fish, control of reproduction requires gametes manipulation (Mohammadi et al, 2015).…”
mentioning
confidence: 99%